Opportunity and Social Mobility - Phelan, Christopher (Review of Economic Studies, 2006)
This paper argues that both inequality of opportunity and social mobility are necessary implications of an efficient, or optimal, societal arrangement when incentives must be provided. ∗The author thanks Marco Bassetto, V.V. Chari, Narayana Kocherlakota and Aleh Tsyvinski for helpful comments. The views expressed herein are those of the author and not necessarily those of the Federal The fact that the children of rich parents have better prospects then the children of poor parents (“inequality of opportunity”) is generally thought to be one of the weak points of modern capitalist societies. On the other hand, the ability of the descendants of poor families to eventually become rich and the descendants of rich families to eventually become poor